High-glucose diets differentially modulate phosphatidylcholine metabolism and fecundity in Caenorhabditis elegans - Wang, Chao-Wen; Chiu, Phebe; Monsalve, Sophia; Roure, Ricardo; Bai, Xiaofei; Law, Jia-Jin; Wu, Yu-Ching; Chen, Yet-Ran; Cheng, You-Liang; Chen, Rey-Huei; Wu, Yi-Chun (Frontiers in Cell and Developmental Biology, 2025)
BackgroundCaenorhabditis elegans fed a high-glucose Escherichia coli OP50 diet exhibit reduced fecundity, but the underlying mechanisms remain unclear.MethodsA differential high-glucose diet paradigm was established using C. elegans fed two bacterial diets that produced distinct fecundity outcomes under high-glucose conditions. The effects of these diets in varying conditions were analyzed through transcriptomic, lipidomic, and metabolomic profiling to correlate with fecundity. Supplementation experiments were further performed to validate the links between changes in lipid metabolism and fecundity. By characterizing the gerlime phenotypes, we constructed a model to interpret how dietary inputs alter oogenesis signaling and, consequently, fecundity outcomes.ResultsC. elegans fed a high-glucose E. coli OP50 diet exhibit reduced fecundity, accompanied by disrupted lipid homeostasis characterized by decreased monounsaturated and increased cyclopropane fatty acids, reduced phosphatidylcholine and elevated triacylglycerols, and abnormal lipid droplet and vitellogenin accumulation in the intestine and oocytes. In contrast, worms fed a high-glucose Comamonas aquatica DA1877 diet maintain lipid balance and normal fecundity. We identified altered lipid metabolism strongly correlated with reproductive decline, whereas dietary signals from C. aquatica protected against glucose toxicity. Mechanistically, high-glucose diets appeared to rewire the choline–methionine axis, lowering PC levels and reducing RAS/ERK signaling in germline and gonadal sheath cells, thereby impairing oogenesis. Notably, vitamin B12 supplementation restored RAS/ERK signaling and rescued the diet-specific fecundity defects.ConclusionWe demonstrate that dietary cues under high-glucose conditions modulate a genetic network linking lipid homeostasis and signaling pathways, ultimately determining fecundity outcomes in C. elegans.